2020
DOI: 10.3390/nano10040810
|View full text |Cite
|
Sign up to set email alerts
|

Biological Safety and Biodistribution of Chitosan Nanoparticles

Abstract: The effect of unmodified chitosan nanoparticles with a size of ~100 nm and a weakly positive charge on blood coagulation, metabolic activity of cultured cardiomyocytes, general toxicity, biodistribution, and reactive changes in rat organs in response to their single intravenous administration at doses of 1, 2, and 4 mg/kg was studied. Chitosan nanoparticles (CNPs) have a small cytotoxic effect and have a weak antiplatelet and anticoagulant effect. Intravenous administration of CNPs does not cause significant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 63 publications
1
25
0
3
Order By: Relevance
“…It was found that the greatest accumulation of NPC-ICG particles occurred in the liver (Figure 17). As expected, the data indicates the elimination of nanoobjects by the liver and confirms the previously obtained data using histochemical staining by Grocott on the predominant accumulation of NPC in the rats' liver [54].…”
Section: Use Of Fluorophore-labeled Nanoparticles For Fluorescent Imasupporting
confidence: 91%
“…It was found that the greatest accumulation of NPC-ICG particles occurred in the liver (Figure 17). As expected, the data indicates the elimination of nanoobjects by the liver and confirms the previously obtained data using histochemical staining by Grocott on the predominant accumulation of NPC in the rats' liver [54].…”
Section: Use Of Fluorophore-labeled Nanoparticles For Fluorescent Imasupporting
confidence: 91%
“…Chitosan, a deacetylated derivative of chitin, is a polysaccharide with both hydroxyl and amine groups in its structure, which play an important role in cross-linking with other molecules, such as proteins, making it suitable for various commercial applications [ 7 ]. In addition, it is non-toxic, hydrophilic, biocompatible, biodegradable, and anti-bacterial [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since lipid nanoparticles were first reported as drug delivery systems in the 1990s, they have attracted wide attention as effective and nontoxic carriers of various drug molecules [ 13 ]. Self-assembled nanoparticles based on poly(lactic– co –glycolic acid) (PLGA) and polysaccharides, which are composed of an inner hydrophobic core and outer hydrophilic shell, have been widely reported to improve drug delivery efficiency [ 14 , 15 , 16 ]. These nanoparticles are also suitable delivery systems for skin wound treatment due to their high drug concentration in the treatment area and the ability to induce tissue repair.…”
Section: Introductionmentioning
confidence: 99%